The effect of the binary space and social interaction in creating an actual context of understanding the traditional urban space - Mustafa Aziz Amen; Dusko Kuzovic (Journal of Contemporary Urban Affairs, 2018)
Urban Space is not just a simple, physical configuration. Instead, it is a transformation of human experiences with the different synchronic architectural characteristic that needs a critical examination to segregate discrete layers of structural elements. As a result, the traditional urban space is a unique existence of reality; it is a product of prolonged interaction between society and architecture. Neglecting any part in the public space perception process is leading to crash the binary equation letting the meaning paralyzed without being able to represent any society or potentially keep the sense. There are many examples of worn-out urban spaces some of them was a result of ignorance and absent of realization of the interaction between Society and architecture.The Iraqi municipality demolished that relationship by importing different layers that are not compatible with the original one or as a result of inserting new means of technology in the heart of the historic cities. The other example from Erbil, a city north of Iraq, where the municipality determinable removed the old fabric to insert a well-defined rectangle space, somehow to create an urban public space, that procedure juxtaposed by form a barrier to isolate the old Souk from the other part of the old city. Both cities suffered from a misunderstanding of the urban binary equation between space and architecture as a tool to understand the context.